2012
DOI: 10.1007/s00428-011-1185-8
|View full text |Cite
|
Sign up to set email alerts
|

KIT protein expression and mutational status of KIT gene in pituitary adenomas

Abstract: KIT protein expression and mutational status of KIT gene in different types of tumours have been intensively studied since Imatinib Mesylate, KIT/PDGFRA tyrosine kinase inhibitor became available. However, only one immunohistochemical study on KIT expression in pituitary adenomas has been published. There are currently no reports on mutational status of KIT gene in pituitary adenomas. We have immunohistochemically investigated KIT expression in 252 pituitary adenomas and found cytoplasmic reactivity in 52.4% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Unlike their study, we found predominant expression of c-kit in NFPA and somatotropinomas, though we have not examined any patient with corticotropinoma and the intensity of positivity varied from tumor subtypes. Similar to our study, Casar et al found cytoplasmic c-kit positivity in 52.4% and membranous positivity in 8.3% (9). Usually it is believed that the mutated protein translocates into the nucleus and gives nuclear positivity.…”
Section: Discussionsupporting
confidence: 92%
“…Unlike their study, we found predominant expression of c-kit in NFPA and somatotropinomas, though we have not examined any patient with corticotropinoma and the intensity of positivity varied from tumor subtypes. Similar to our study, Casar et al found cytoplasmic c-kit positivity in 52.4% and membranous positivity in 8.3% (9). Usually it is believed that the mutated protein translocates into the nucleus and gives nuclear positivity.…”
Section: Discussionsupporting
confidence: 92%
“…Patients with Nelson’s syndrome were included in the previously established cohort, while only adult patients with corticotroph functioning PitNETs were used for the present comparison. Moreover, only limited clinical data (gender, age, tumour size (micro/macro)) were available for the corticotroph functioning PitNETs [ 23 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…The original haematoxylin eosin stained sections from all tumours were reviewed to confirm the presence of pituitary tumour tissue. TMAs were constructed containing replicate 1 mm cores from formalin-fixed paraffin embedded tissue samples from representative areas [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…35 However, it is worth noting that CD117 expression, not associated with c-kit mutation, has also been documented in a subgroup of ACTH pituitary adenomas. 36,37 The meaning of CD117 expression in corticotrophs is not clear, nor is its expression in PanNETs. The monoclonal antibody 331.3, recognizing the COOH-terminal portion of both BCL10 and carboxyl ester lipase, is useful to identify pancreatic acinar cells and ACCs.…”
Section: Acth-secreting Accmentioning
confidence: 99%